MANAJEMEN HUBUNGAN SEKOLAH DAN MASYARAKAT DALAM MENINGKATKAN MUTU PENDIDIKAN PADA SMP NEGERI 13 BANDA ACEH - Sulaiman Bakri, Cut Zahri Harun, Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
Abstract: The management of public relations is an important factor in improving the quality of education at schools. The management of public relations is to establish a relationship with the community in order to get support in improving the quality of education, e.g., the quality of the learning process, student learning outcomes, and the community itself. The purpose of this study was to obtain an idea and know how program, implementation, and obstacles of public relation management between school and community in improving the quality of education at SMPN 13 of Banda Aceh. This study used a qualitative approach. The techniques of collecting data were done through observation, interviews, and documentation. The subjects in this study school were principal, vice- principal of Public Relation Affairs, School Committee, and community leaders. The results showed that: (1) the school-community relations program has been designed by rejuvenating of the board of the school committee, regular meetings at the beginning of each school semester by involving all school stakeholders, fostering transparency in the management of the school; (2) The implementation of the management of the school-community relations (Public Relations) were to empower the activities of the school committee, require parents of the students to pick up report cards by themselves, inform progress and derogation of students to parents and school committee, provide information about the state of school to school committees and communities and celebrate religious holy days; (3) The obstacles faced in the implementation of public relations management were that some parents still did not yet have a high awareness of contributing to improve the quality of education at schools and would not come if there were parents and committee meetings, as well as other school activities. Keywords: management, relationship between the school and the communityAbstrak: Manajemen kehumasan merupakan faktor penting dalam upaya peningkatan mutu pendidikan di sekolah. Manajemen kehumasan untuk menjalin hubungan dengan masyarakat, guna mendapat dukungan dalam peningkatan mutu pendidikan. Baik peningkatan kualitas proses pembelajaran, kualitas hasil belajar siswa, dan kualitas masyarakat itu sendiri. Penelitian ini bertujuan untuk mendapat gambaran dan mengetahui bagaimana program, pelaksanaan, dan hambatan manajemen hubungan sekolah dan masyarakat dalam meningkatan mutu pendidikan pada SMP Negeri 13 Banda Aceh. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data dengan observasi, wawancara, dan dokumentasi. Subjek dalam penelitian ini Kepala sekolah, Wakil kepala sekolah bidang Humas, Komite sekolah, dan tokoh masyarakat. Hasil penelitian menunjukkan bahwa: (1) Program hubungan sekolah dan masyarakat telah dirancang meliputi: pemilihan pengurus komite sekolah, rapat rutin sekolah tiap awal semester dengan melibatkan seluruh stakeholder sekolah, menumbuhkan transparansi pengelolaan sekolah;. (2) Pelaksanaan manajemen hubungan sekolah dan masyarakat (humas) meliputi kegiatan pemberdayaan komite sekolah, mewajibkan orang tua mengambil rapor anak sendiri, mengimformasikan kemajuan dan kemunduran siswa kepada orang tua dan komite sekolah, penyediaan informasi tentang keadaan sekolah kepada komite sekolah dan masyarakat serta memperingati hari-hari besar keagamaan; (3) Hambatan yang dihadapi dalam pelaksanaan manajemen humas, masih ada sebahagian orang tua siswa belum memiliki kesadaran yang tinggi untuk ikut serta meningkatkan mutu pendidikan di sekolah dengan tidak mau hadir saat ada pemanggilan orang tua dan rapat komite, serta kegiatan sekolah lainnya.Kata kunci : manajemen, hubungan sekolah, dan masyarakat